Right hepatic artery encircle the gallbladder: a case report - Mohd Nor, Mohd Hanis; Amjad, Nasser Muhammad (Kulliyyah of Medicine, International Islamic University Malaysia, 2019)
Detailed knowledge of the vascular anatomy of hepatobiliary system is important for a safe cholecystectomy. We are reporting a case of aberrant type of right hepatic artery originating from superior mesenteric artery and encircles the gallbladder that has been found during laparoscopic cholecystectomy operation. We presented a 39-year-old Malay lady came to International Islamic University Malaysia Medical Centre with features of obstructive jaundice. Ultrasound of hepatobiliary system showed cholelithiasis with choledocholithiasis causing dilatation of the common bile duct. ERCP had been performed and sphincterotomy was done. Patient was planned for laparoscopic cholecystectomy. Intraoperatively, the Calot’s triangle was identified in usual manner. However, the right hepatic artery was identified encircling the gallbladder body anteriorly before entering the liver. The procedure was converted to open cholecystectomy due to anatomical variation via Kocher’s incision. Further identification upon open cholecystectomy revealed right hepatic artery originates from superior mesenteric artery runs anterior to cystic duct and encircles the gallbladder before further branches into right and left lobe of the liver. Right hepatic artery was dissected from the gallbladder and the gallbladder removed after cystic duct ligation and separation from the liver bed. On table cholangiogram showed distal CBD stone which was pushed down to duodenum with forceps? Post-operative was uneventful and patient liver functions improved. Knowledge regarding anatomical structure and variant of hepatic artery as well as cystic artery and cystic duct is important to ensure the inadvertent ligation of right hepatic artery which would leads to hepatic ischemia and necrosis.